The Role of Social Studies Teachers in Shaping the Awareness of Student National Integration in the Globalization Era - Rishayati, Siti; Nuryana, Nuryana; Hatami, Wisnu (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2023)
This research is motivated by the lack of student awareness of the importance of national integration, the occurrence of disputes between students of different regions and languages, students are more likely to do individualist attitudes that are selfish, to love and boast excessively in other people's countries than their own country. This study aims to determine the role of social studies teachers in shaping students' national integration awareness in the era of globalization at SMP Negeri 1 Ciledug, especially the form of students' national integration awareness in the era of globalization, and the supporting and inhibiting factors in shaping students' national integration awareness in the era of globalization at SMP Negeri 1 Ciledug. This research uses a qualitative method, with a case study approach. The awareness of national integration needs to be formed in students in order to create a harmonious unity, harmony and uniformity, a sense of comfort, mutual help, mutual respect, mutual cooperation, and mutual respect. Because basically the essence of national integration is the same as Bhineka Tunggal Ika which means different but still one goal. But the reality is that there are still many students who lack awareness of national integration so that disputes and divisions occur. So the need for the role of educators, especially social studies teachers is very important in realizing and preparing students to be able to become good citizens in a society that has a variety of differences.